Making a website as a marketing effort for Kuro Potret SMEs - Tony Soebijono; Martinus Sony Erstiawan; Aldi Irwantono Saputra (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2021)
Kuro Potret is a Small Medium Entreprise (SME) located in Sidoarjo which is engaged in photography and videography services. Until now Kuro Potret SME only does marketing through social media, and has problems marketing its services. To make purchase order for photography or videography services, a customer must still have to contact and meet directly with this SME, then the SME will record service orders and schedule their services manually. Based on these problems, a website-based marketing application is needed for Kuro Potret SME, which can record and schedule photography service orders. The method used in implementing this marketing application is direct training to the community as the end user in Kuro Potret SME teams. The results achieved are: From the Kuro Potret SME side, the satisfaction level of using the application is 90% while 10% states that the application needs to be equipped with better training modules. But from the consumer side of the 30 application users, 80% of marketing application users find it helpful to get to know the Kuro Potret SME more closely, 20% of application users say that the appearance still needs to be improved. From 80% of users, 25% order photography services to this SME.